X/2 - y/3 = 3/2X/3 + y/2 = 16/3
1 answer:
X/2-y/3=3/2
(6×x/2)-(6×y/3)=6×3/2
3x-2y=9______(1)
x/3+y/2=16/3
(6×x/3)+(6×y/2)=6×16/3
2x+3y=32_____(2)
(1)×3____9x-6y=27____(3)
(2)×2____4x+6y=64____(4)
(3)+(4)___13x=91
x=7
3(7)-2y=9
-2y=-12
y=6
You might be interested in
Answer:
52
Step-by-step explanation:
52 52 52 52 52 52 52 52
Answer:
its -0.4, are those rlly the options? if they are jus round up and do -1
Answer:
23 and 33
Step-by-step explanation:
23+33=56
33-23=10
The awnser is A) and C)
Hope it helps :)